Konstruksi Citra Sekolah SDIT Melalui Strategi Komunikasi Pemasaran Berbasis AI - Astri Octaviani; Nabila Sekar Arum Hasanah; Munaldi Munaldi (Journal of Innovative and Creativity (Joecy), 2026)
The study purpose was to analyze the construction of school image at Integrated Islamic Elementary Schools (SDIT) through artificial intelligence-based marketing communication strategies, particularly in the context of digital branding and public trust building. Materials and methods. This study used a descriptive qualitative method with a constructivist paradigm. Data were collected through digital observation of school social media and website content, in-depth interviews, documentation, and literature review related to educational branding, organizational image, and artificial intelligence in marketing communication. Results. The findings show that SDIT Qur’an Mumtaz Robbani has used AI through website optimization supported by SEO, generative AI for promotional copy and visual design, social media engagement analysis, content scheduling, and chatbot-based information services. These practices help the school deliver information more efficiently, build interaction with parents, and represent itself as a modern, religious, responsive, and innovative Islamic educational institution. Conclusions. AI-based marketing communication contributes to the construction of a competitive school image in the digital era. The school image is formed through repeated digital symbols, visual content, religious narratives, and responsive communication that shape public perception and trust toward the institution.